Dividend as a Moderation Variable to Increase Stock Prices - Yuliana, Indah; Indiyanto, Agus; Yusuf, Mirna; Prajawati, Maretha Ika (Jurnal Keuangan dan Perbankan, 2021)
One of the strategic decisions in the company is related to dividend decisions. It becomes the basis for investors to invest in shares. Investors value income from dividends distributed by companies for more than income from capital gains. Investors prefer to receive payment now than future ones because they are faced with uncertainty. Regular dividend distribution indicates the company has bright prospects in the future. Accordingly, Dividends have a significant influence on the increase in share prices. Data were collected using the documentation method of 34 samples of the most liquid Islamic stocks listed on the IDX. This research uses the SPSS analysis technique and uses a partial test (t-test). The tests to determine the significance of each independent variable in influencing the dependent variable with a one-way test and using moderation regression to test and analyze the effect of dividends per share on stock prices, whether to strengthen/weaken the dependent variable. The study results found that profitability and solvency , as well as dividends, have a relationship with stock prices. The relationship between ROA and share prices as moderated by dividends is negative for stock prices. The relationship between ROE and share price, which is moderated by dividends, is positive but not significant. Dividends can significantly strengthen the DER relationship to the share price. In addition, dividends were able to strengthen DAR's relationship with share prices significantly.JEL: G11, G12, G41